2019
DOI: 10.1017/s1047951119001471
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers improve prediction of 30-day unplanned readmission or mortality after paediatric congenital heart surgery

Abstract: Objective: To evaluate the association between novel pre-and post-operative biomarker levels and 30-day unplanned readmission or mortality after pediatric congenital heart surgery. Methods: Children aged 18 years or younger undergoing congenital heart surgery (n=162) , at Johns Hopkins Hospital from 2010–2014 were enrolled in the prospective cohort. Collected novel pre-and postoperative biomarkers include: soluble suppression of tumorgenicity 2, Galectin-3, N-terminal prohormone of brain natriuretic peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…An understanding of a child's statistically anticipated risk of readmission or mortality may aid in determining the appropriate time for surgery, surgical alternatives and individualised operative care, and hospital release guidelines. A similar finding was made by Brown et al (10) .…”
Section: Table (7): Association Between Change Between Pre and Post-o...supporting
confidence: 89%
“…An understanding of a child's statistically anticipated risk of readmission or mortality may aid in determining the appropriate time for surgery, surgical alternatives and individualised operative care, and hospital release guidelines. A similar finding was made by Brown et al (10) .…”
Section: Table (7): Association Between Change Between Pre and Post-o...supporting
confidence: 89%
“…Adding one additional recommended article 31 , we found that this results in 109 records being included in the full-text assessment. Among the 84 excluded records, 2 were predictive model studies for 30-day HRs (ie, UHRs and planned HRs) with discrimination metrics 32 33 ; 12 studies analysed 30-day UHRs or 30-day HRs combined with another outcome (ie, emergency department return visits (n=5), 34–38 mortality (n=3) 39–41 and other complications (n=4) 42–45 ); 3 were predictive model studies for 30-day UHRs or 30-day HRs with no discrimination metrics 46–48 ; 5 were non-regression-based predictive model studies for 30-day UHRs or 30-day HRs in paediatrics 21 49–52 ; and 59 were prognostic factor studies for 30-day UHRs or 30-day HRs. Based on the full-text assessments (n=25) and the hand search of reference lists (n=3 53–55 ), 28 studies were included in the systematic review, with 6 of them 55–60 already presented in a previous systematic review 3 with a different focus.…”
Section: Resultsmentioning
confidence: 99%
“…8 Additionally we found that pre-and postoperative ST2 was associated with unplanned 30-day readmission or death, whereas NT-proBNP was not useful in predicting 30-day readmission or death. 17 This evaluation of the utility of length of stay provides new insight to our team's guidance on the use of biomarkers, especially the utility of ST2, using an outcome variable with limited literature surrounding it.…”
Section: Commentmentioning
confidence: 99%